2016
DOI: 10.1002/1873-3468.12106
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the pathogenic mutation T372R in the Yin Yang 1 protein interaction with DNA – thermodynamic studies

Abstract: Edited by Alfonso ValenciaThis work focuses on the pathogenic missense mutation in YY1 protein correlated with insulinomas. Based on in vitro studies, we demonstrate that the mutation does not affect the secondary structure of either zinc fingers or the N-terminal fragment (NTF) of the protein. Apart from a slight increase in the protein's compactness, no changes in the tertiary structure were observed. The introduced mutation significantly alters DNA-binding properties, both the affinity and enthalpy-entropy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Surprisingly, labeling efficiency of cysteine variants was significantly higher for NTFs than for YY1s, regardless of the location of the engineered cysteine residue and labeling conditions, despite the full‐length protein contain zinc fingers, which are (may be) also subjected to labeling. These observations may indicate the presence of interactions between the N‐ and C‐terminal fragments of YY1, as postulated previously . Such interactions can restrict the access of the label to the introduced cysteine residues.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Surprisingly, labeling efficiency of cysteine variants was significantly higher for NTFs than for YY1s, regardless of the location of the engineered cysteine residue and labeling conditions, despite the full‐length protein contain zinc fingers, which are (may be) also subjected to labeling. These observations may indicate the presence of interactions between the N‐ and C‐terminal fragments of YY1, as postulated previously . Such interactions can restrict the access of the label to the introduced cysteine residues.…”
Section: Discussionsupporting
confidence: 70%
“…The only exception was the S14C mutant, when r0app values were greater for NTF than for YY1 in both tested salt concentrations. This discrepancy may indicate direct interactions between the N‐ and C‐terminal fragments of YY1, which have been postulated previously . The difference of the r0app values observed only for this mutation may indicate that the vicinity of the S14 residue is involved in the intramolecular interaction.…”
Section: Discussionmentioning
confidence: 46%
“…Mutation of threonine to arginine at 372 positions of YY1 had been shown to inhibit DNA binding of YY1. 33 Thus, we further examined GLUT3 transcriptional activity in HCT116 p53null cells overexpressing mutant YY1 T372R (Supplementary Figure S5A) We found that YY1 T372R overexpression could not significantly affect the luciferase activity of GLUT3 reporter ( Figure 5H), as well as its mRNA expression level ( Figure 5I), indicating that YY1 directly regulates GLUT3 transcription. Concomitantly, YY1 T372R could not upregulate glucose consumption and lactate production ( Supplementary Figure S5B,C).…”
Section: Yin Yang 1 Directly Affects Glucose Transporter 3 Transcrimentioning
confidence: 98%
“…Our research group established a protocol for robust production of active, recombinant YY1 protein (Golebiowski et al, 2011) as well as a sensitive, quantitative equilibrium assay for YY1-DNA interaction (Golebiowski et al, 2012). These methods previously allowed us to precisely analyze the effect of another YY1 mutation, T372R, which is recurrent in insulinomas, and proved it to affect YY1 binding to DNA in a sequence-specific way (Nieborak & Gorecki, 2016). In this paper, we analyzed the impact of D380Y mutation on YY1 structure and its interaction with DNA.…”
Section: Introductionmentioning
confidence: 99%